2021
DOI: 10.1021/acs.jpcc.1c01675
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Guest Localization in Mesoporous Silica Particles by Solid-State NMR and Ab Initio Modeling: New Insights into Benzoic Acid and p-Fluorobenzoic Acid Embedded in MCM-41 via Ball Milling

Abstract: We present a novel strategy for mapping the localization of guest molecules (GMs) in mesoporous materials by combining mechanochemistry with solid-state nuclear magnetic resonance (ssNMR) spectroscopy. To this end, we consider model guest–host systems of benzoic acid (BA) and para-fluorobenzoic acid (4-FBA) embedded in mesoporous MCM-41 material and examine the recently proposed loading (MeLo) procedure for efficient encapsulation of molecular species. Application of high-resolution NMR experiments (1H and 19F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…The maximum capacity of loading was over 50% at a 1:1 ratio. Moreover, it has been proven that using this technique, guest molecules are located in different zones of MCM-41 particles (Figure 4) [122]. Hedous et al demonstrated that the co-milling of SBA-15 with ibuprofen made it possible to load the drug into the porous matrix, enhancing thereby the filling degree to almost 40 wt% [59].…”
Section: Solvent-free Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum capacity of loading was over 50% at a 1:1 ratio. Moreover, it has been proven that using this technique, guest molecules are located in different zones of MCM-41 particles (Figure 4) [122]. Hedous et al demonstrated that the co-milling of SBA-15 with ibuprofen made it possible to load the drug into the porous matrix, enhancing thereby the filling degree to almost 40 wt% [59].…”
Section: Solvent-free Methodsmentioning
confidence: 99%
“…Co-milling is a commonly used technique to produce sub micrometric particles [120] as well as for solid-state amorphization [121]. Recent studies have shown that milling using a planetary ball mill is an effective solvent-free method for introducing organic compounds such as benzoic acid and 4-fluoro benzoic acid into the pores of MCM-41 [122]. This study also appeared that the guest-loading process is fully controlled and dependent on the ratio of the loaded substance and silica.…”
Section: Solvent-free Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper shows that the innovative MAL method, developed by the authors, is a very efficient and unique solid-state method for loading molecular materials within mesoporous silica matrices, as recently confirmed in a very recent study performed by another group. 26 It is now recognized as an alternative to solvent-based drug loading methods, and considered as very useful for pharmaceutical applications. 27,28 We show that using this solid-state method makes possible to confine the selected crystalline form of a polymorphic system.…”
Section: Discussionmentioning
confidence: 99%
“…The Buntkowsky group used 1D and 2D multinuclear magic-angle spinning (MAS) NMR to monitor the synthesis of the novel Wilkinson’s type silica supported polymer catalysts . The guest localization in mesoporous silica particles was mapped by 1 H and 19 F MAS NMR by the Potrzebowski group . The Sun group investigated the structure–property relationship of chitosan-based biopolymers .…”
mentioning
confidence: 99%